2015
DOI: 10.1007/s13277-015-3079-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of soluble H7-B4 in pleural effusion associated with lung cancer

Abstract: B7-H4, a member of the inhibitory B7 family, can restrain T cell proliferation, activation, and cytokine secretion and may be involved in immune evasion in cancer patients. This study aimed to evaluate the diagnostic and prognostic value of pleural effusion levels of soluble B7-H4 (sB7-H4) in lung cancer patients with malignant pleural effusion (MPE). Pleural effusion samples were collected from 98 lung cancer patients with malignant effusion and from 60 patients with nonmalignant pleural effusion. Pleural eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In our study, we obtained an optimized cutoff value of sB7‐H4 36.5 ng/ml and CEA 4.18 ng/ml to differentiate MPE from BPE with a corresponding sensitivity (81.82%, 87.28%) and specificity (90.48%, 95.24%). This was consistent with the report by Xu et al, in which exhibited a sensitivity of 78.6% and a specificity of 91.7% of sB7‐H4 for MPE associated with lung cancer with a cutoff point 35.8 ng/ml.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, we obtained an optimized cutoff value of sB7‐H4 36.5 ng/ml and CEA 4.18 ng/ml to differentiate MPE from BPE with a corresponding sensitivity (81.82%, 87.28%) and specificity (90.48%, 95.24%). This was consistent with the report by Xu et al, in which exhibited a sensitivity of 78.6% and a specificity of 91.7% of sB7‐H4 for MPE associated with lung cancer with a cutoff point 35.8 ng/ml.…”
Section: Discussionsupporting
confidence: 92%
“…B7‐H4, which belongs to a novel member of the inhibitory B7 family, plays an important role in the process of modulating the tumor cellular immune response . Previous studies had confirmed that B7‐H4 overexpressed in various human malignant tumors including non‐small‐cell lung cancer, breast, esophageal, gastric, bladder, osteosarcoma, hepatocellular, and so on, which were notably related to tumor malignant degree, progression, and prognosis, while not expressed or down‐regulated in normal human tissues . In recent years, sB7‐H4 was regarded as a potentially valuable tumor marker .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, sB7-H4 was also correlated with serum AFP levels in HCC, distant metastasis at nephrectomy in RCC, distant metastasis in osteosarcoma, and histology type in ovarian cancer ( 247 , 248 , 250 , 252 , 254 ). Soluble B7-H4 levels in malignant pleural effusion were higher in lung cancer and predicted a worst prognosis ( 255 ). Elevated preoperative levels had predicted a worse response to anti-VEGF therapy in RCC ( 250 ).…”
Section: Soluble B7-h4mentioning
confidence: 99%
“…It has also been reported that the expression of B7-H4 is associated with TNM staging and the pathological grading of bladder cancer and thyroid cancer [ 29 , 30 ]. Additionally, soluble B7-H4 can be used as a diagnostic and prognostic marker of malignant pleural effusion [ 31 ]. However, the expression and the potential role of B7-H4 in LC development have not been reported.…”
Section: Discussionmentioning
confidence: 99%